REGULATION OF RELATIONS OF PROPERTY ON NATURAL RESOURCES IN TRANSFORMATION ECONOMICS - M. A. Baishew (Russian Journal of Economics and Law)
The problems of solving ecology-economic contradictions, problem of property on natural resources are considered in the article. The ways of solving these problems are offered.